?NEW n.ECORDS OF COPROPHILOUS FUNGI FROM TURKHAM, NORTH PAKISTAN - Masood, Ahmadunnisa; Ahmed, SI; Qadri, R B (Biological Sciences - PJSIR, 1998)
Sixteen genera and 24 species f Ascomycetous fungi arc reported from Turkham on goat dung substrate. These fungi have never been reported earlier from this region, The species reported in this paper include: Ascoholus inunersus pel's; Ascodesmis porcino Seaver, Coprotus granuliformis (Cr. & Cr.) Kimbrough, Cliaetomium splrale Zopf Chaetotnium globosuin Kunze Fr., Delitsch!a marchalii Berl. and Vogi., Kernia nitida (Sacc.) Nicuwland, Lophotrichus bartlettii (Massce & Salmon) Mollaeh & Cain, Podospora pretliopodalis Cain, Sonia ria [imicola (Rob.) Ces. and de Nolo, Saccobolus versicolor (Karst.) Karst. Sporormia [unetaria De Not., Sporormiella australis (Spcg.) Ahmed and Cain, Sporortniella dakotensis (Griff.) Ahmed and Cain, Sporonniella minima (Aucrsw.) Ahmed and ain, Sporonuiella capybarae (Spcg.) Ahmed and Cain, Sporormiel!a hexamera Ahmed et al. Spororiniella tetramera Ahmed and Cain, Sporormiella inaequalis Ahmed and Asad, Sporormiella interniedia (Auersw.) Ahmed ana Cain, Thielavia variospora Cain, Tripterospora erostrata (Griff.) Cain, Zopfiella karachiensis (Ahmed & Asad) Guano and Zygopleurage nuilticaudata Mirza.